AN An Analysis of Adjacency Pairs in The Conversation between David Frost and Paul Mc.Cartney - siahaan, junita (UICELL, 2018)
This study investigated about the adjacency pairs in the conversation between David Frost and Paul Mc.Cartney. The aims of this study are to find out what types of adjacency pairs appeared in the conversation and what types of communicative function contained in the conversation between David and Paul. This research used qualitative descriptive method as a research design. The data were a video containing conversation between David Frost and Paul Mc.Cartney. The data were transcribed into written form and analyzed using theory of adjacency pairs and communicative function. The findings of this research revealed that: first, there were two types of adjacency pairs appeared in the conversation. From those two types of adjacency pairs, there were 12 adjacency pairs that represent question-answer; 2 adjacency pairs represent Assessment-Agreement/Disagreement. Second, for communicative function, there were 14 referential function contained in the conversation, followed by phatic functions with 3 occurrences, 1 occurrence for each emotive function and metalingual function. From the finding, it can be concluded that question-answer was the mostly-appeared type of adjacency pairs in the conversation between David Frost and Paul Mc.Cartney and Assessment-Agreement/Disagreement were the least pairs. While for communicative function, referential function was the mostly-served function in the conversation.   Keywords: Discourse Analysis, Adjacency pairs, Conversation